Inovasi Pelayanan Program Three In One ( 3 in 1) Di Dinas Kependudukan dan Catatan sipil Kota Bengkulu - Titi Darmi; Aldo Nopiansa; Kasman (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2024)
This study aims to examine the innovation of Three In One (3 In 1) Services and the supporting and inhibiting factors of Three In One (3 In 1) Service innovation in population administration services in Bengkulu City. This study uses data collection methods in the form of observation, interviews, and documentation. The results of the study show that communication between the Population and Civil Registration Service of Bengkulu City is carried out with several supporting institutions. Resources are sufficient and in accordance with Standard Operating Procedures (SOP), Three In One (3 In 1) Services can increase the scope of ownership of Death Certificates, Family Cards (KK), and Identity Cards (divorce and death), services are carried out in a short time and do not use administration fees/free. The response given by the community to the Three In One (3 In 1) Service has mostly given a positive response. The community can receive 3 (three) documents, namely Death Certificates, Family Cards (KK), and Identity Cards (KTP) for Divorce and Death. The implementation is supported by the Population and Civil Registration Service of Bengkulu City conducting socialization in collaboration with the Sub-districts and Urban Villages of Bengkulu City. The obstacles faced are the lack of public understanding of the importance of owning a Death Certificate.